LPC-DHA/EPA-Enriched Diets Increase Brain DHA and Modulate Behavior in Mice That Express Human APOE4 - Scheinman, Sarah B.; Sugasini, Dhavamani; Zayed, Monay; Yalagala, Poorna C. R.; Marottoli, Felecia M.; Subbaiah, Papasani V.; Tai, Leon M. (Frontiers in Neuroscience, 2021)
Compared to APOE3, APOE4 is associated with greater age-related cognitive decline and higher risk of neurodegenerative disorders. Therefore, development of supplements targeting processes modulated by APOE genotype could be beneficial for the aging population. Evidence suggests a link between APOE genotype and docosahexaenoic acid (DHA), however, clinical studies with current DHA supplements have produced negative results in dementia. Lack of beneficial effects with current DHA supplements may be related to limited bioavailability, as the optimal form of DHA for brain uptake is lysophosphatidylcholine (LPC)-DHA. We previously developed a method to enrich the LPC-DHA content of krill oil through lipase treatment (LT-krill oil), which resulted in 5‐fold higher enrichment in brain DHA levels in wild type mice compared to untreated krill oil. Here, we evaluated the effect of a control diet, diet containing krill oil, or a diet containing LT-krill oil in APOE3- and APOE4-targeted replacement mice (APOE-TR mice; treated from 4 to 12 months of age). We found that DHA levels in the plasma and hippocampus are lower in APOE4-TR mice, and that LT-krill oil increased plasma and hippocampal DHA levels in both APOE3- and APOE4-TR mice. In APOE4-TR mice, LT-krill oil treatment resulted in higher levels of the synaptic vesicle protein SV2A, and improved performance on the novel object recognition test. In conclusion, our data demonstrate LPC-DHA/EPA enriched-krill oil can increase brain DHA and improve memory-relevant behavior in mice that express APOE4. Therefore, long-term use of LT-krill oil supplements may on some level protect against age related neurodegeneration.